2009
DOI: 10.1002/prca.200800190
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach combining MS and bioinformatic analysis for the detection and identification of biomarkers of administration of exogenous human growth hormone in humans

Abstract: An integrated MS-based proteomic approach is described that combines MALDI-MS and LC-MS with artificial neural networks for the identification of protein and peptide biomarkers associated with recombinant human growth hormone (rhGH) administration. Serum from exercised males administered with rhGH or placebo was analysed using ELISA to determine insulinlike growth factor-I concentrations. Diluted serum from rhGH-and placebo-treated subjects was analysed for protein biomarkers by MALDI-MS, whereas LC-MS was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, rbST immunoassays were not capable to distinguish the almost identical recombinant and endogenous forms of bST [19], [20], [24], [25] and mass spectrometry-based methods on the other hand required very tedious sample preparation procedures [26], [27]. For screening of rbST in cattle, a few biomarker-based methods were developed, but focused on a single candidate biomarker only [4], [9], [28][30]. In a recent study, three candidate biomarkers were combined in one screening tool, but the <5% false-compliant rate target could not be achieved [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rbST immunoassays were not capable to distinguish the almost identical recombinant and endogenous forms of bST [19], [20], [24], [25] and mass spectrometry-based methods on the other hand required very tedious sample preparation procedures [26], [27]. For screening of rbST in cattle, a few biomarker-based methods were developed, but focused on a single candidate biomarker only [4], [9], [28][30]. In a recent study, three candidate biomarkers were combined in one screening tool, but the <5% false-compliant rate target could not be achieved [31].…”
Section: Introductionmentioning
confidence: 99%
“…The ACN depletion method used in this study has been shown to enrich the serum concentrations of a number of low molecular weight proteins prior to nano‐LC/MS/MS analysis 21. The depletion technique (in combination with ANN analysis) was applied successfully to the identification of LRG as a biomarker to rhGH abuse in humans 14. We have further demonstrated that ACN depletion, in combination with tryptic digestion and uHPLC/MS/MS with SRM detection, may be used for the quantitative analysis of serum proteins in large sample cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…A biomarker discovery study performed by our laboratories identified the protein leucine‐rich α‐2‐glycoprotein (LRG) as a putative biomarker of rhGH administration through the use of liquid chromatography/mass spectrometry (LC/MS) and artificial neural networks (ANNs) 14. To confirm LRG as a true biomarker of rhGH abuse, samples from additional administrations would need to be analysed.…”
mentioning
confidence: 99%